Learning of Reading Comprehension through Reading Workshop in the Industry 4.0 - Setiyadi, Ruli; Kuswendi, Uus; Ristiana, Muhammad Ghiyats (Mimbar Sekolah Dasar, 2019)
Reading comprehension is still considered as a part of new literacy required to encounter the Industry 4.0. Reading comprehension in this era is related to reading the data presented in technology. In addition to students ability to understand readings, students sort positive and negative information in a reading through reading comprehension. Students can also get used to utilize the internet access to read various information and stories. Therefore, the presence of the Industry 4.0 is considered to not have negative effects on students. This research focuses on examining the online magazine-based reading workshop model towards the improvement of fourth grade students reading comprehension skills. The research employed quasi experiment methods with a nonequivalent group design. The research sample was selected purposively from fourth grade students in primary schools in Cimahi City. The data were collected using the test of reading comprehension skills and were analyzed using inferential statistics with the assistance of the SPSS 21.0 program. Through this research, the researchers are expected that the online magazine-based reading workshop model has an effect on the improvement of the fourth-grade students reading comprehension skills.